Techno-economic analysis of marine hybrid clusters in two potential Latin American markets (Proceedings of the European Wave and Tidal Energy Conference, 2023)
Contemporary communities require innovative solutions to cope with projected increases in demand for natural resources. Diversification and modernization of the energy matrix through the affordable and efficient harnessing of marine renewable energies (MRE) are possible means to mitigate the vulnerability of coastal communities and climate change. While the offshore wind sector has reached sufficient maturity to compete in the energy market, other MRE, such as wave energy, are still in the development phase, which limits their financing and commercial deployment. This study aims to evaluate the techno-economic feasibility of maritime hybrid clusters (MHC) powered by wave energy converters (WEC) and offshore wind turbines (OWT) to electrify households and the marine aquaculture sector, where electricity surpluses can be stored in lithium-ion batteries or for green hydrogen production. Different scenarios for WaveDragon (WD) and Pelamis (PEL) WEC farms were studied in two coastal communities, Coquimbo (Chile) and Ensenada (Mexico). The mean annual wave power availability at Coquimbo is high (26.05 kW/m) and of Ensenada, moderate (13.8 kW/m). The wave energy shows less inter- and intra-annual variability in Coquimbo than in Ensenada. The hybridization between WECs and OWT covers the total electricity consumption, where the PEL-OWT system is the cost-effective option in Ensenada and WD-OWT in Coquimbo. Ensenada demonstrated a higher electricity surplus than Coquimbo, profitable result of storing it to sale in the electricity market or for hydrogen production. For both selected WECs, the seaweed aquaculture integration in a blue economy framework generates higher returns than households, higher in Coquimbo than Ensenada.